Program Siaran Interaktif (Talk Back Radio) Sebagai Ruang Publik Masyarakat Untuk Mengembangkan Demokrasi Lokal: Studi Pada Program ”Citra Publika” Radio Citra 87,9 FM Kota Malang - Rochmad Effendy (Jurnal Komunikasi, 2014)
As social institution, national press should serve pubic interest by meeting the people’s right to know in the form of news which concerns the lives of the people. In addition to that, press is also required to serve public to spare its pace and time for people to express their voices and grievances regarding public issues. Due to its interactivity and hyper-local journalism, radio can perform this well. Talkback radio broadcasts containing interaction between the host broadcaster with the listener expressing their concerns and information on public issues have been able to encourage the process of local democratization. As such “Citra Publika" has been able to encourage citizens not only to exercise social control and take part in debating public concerns but also ask them to give solution the public problems. The research which used a qualitative approach with some informants form Citra FM radio has found that that listeners not only are asked to express their information and concerns but also are invited to provide solutions to these problems. Announcer then made every effort to contact the relevant parties to confirm the citizen complaint information. But managerial conflict within the radio has made the talkback radio unable to operate optimally. Unfortunately, to make things even worse, the conflict has led to cessation of broadcasting activities.